Screening schizotypal personality disorder for detection of clinical high risk of psychosis in Chinese mental health services. Issue 3 (30th August 2015) - Zhang, TianHong; Li, HuiJun; Tang, YingYing; Li, Hui; Zheng, LiNa; Guo, Qian; Zhao, ShanShan; Zhuo, KaiMing; Qian, ZhenYing; Wang, LanLan; Dai, YunFei; Chow, Annabelle; et al.
Abstract: Schizotypal personality disorder (SPD) is viewed as a marker of prodromal psychosis. However, information regarding genetic risk (e.g. SPD) is often overlooked in the identification process. This study assessed whether SPD screening questionnaire help the prodromal psychosis (also widely applied "clinical high risk" (CHR) for clinical sample) detection in Chinese mental health service. This work also examined whether SPD had higher frequency in genetic risk population and CHR subjects. Two wave studies concerning the SPD identification was used for analysis. Wave 1 survey: 3075 subjects were assessed by Personality Diagnostic Questionnaire for SPD (PDQ-SPD) and Structured Clinical Interview for DSM-IV Axis II (SCID-II). Wave 2 survey: 2113 subjects screened with the prodromal questionnaire -brief version (PQ-B), PDQ-SPD, and interviewed by Structured Interview for Prodromal Symptoms (SIPS). Subjects with family history of mental disorders or with psychosis reported significantly higher scores in SPD. Receiver operating characteristic curves suggested that PDQ-SPD had moderate sensitivity and specificity for identifying CHR subjects. There was significant higher on SPD features in subjects with early stage (Course less than 1 year) of psychosis. Identifying SPD may be useful in early detection of psychosis especially in detecting the genetic risk syndromes and can be integrated with existing prodromal screen tools to improve its efficiency. Highlights: ● The identification of SPD is useful for screening prodromal psychosis. ● A short form can be integrated into existing screen tools for prodromal psychosis. ● SPD screening could make early detection of psychosis more efficient.